Pengaruh Total Quality Management (TQM), Motivasi Kerja, dan Komitmen Organisasi Terhadap Kinerja Manajerial - Fanny Effiandi; Randy Heriyanto; Novrina Chandra (CV. ALIM'SPUBLISHING, 2024)
This study aims to determine the effect of Total Quality Management (TQM), work motivation, and organizational commitment on managerial performance at PT Semen Padang using a quantitative approach method. The population in the study were all managers and senior managers working at PT Semen Padang totaling 140 people. In this study, the sampling technique used the purposive sampling method. The sources in this study were employees who held managerial positions at PT Semen Padang. The data collection method that will be used in this study is a questionnaire. Data were processed using SPSS 25.0. The results of the study indicate that Total Quality Management and work motivation have a positive and significant effect on managerial performance, organizational commitment does not have a significant effect on managerial performance. Total quality management, work motivation and organizational commitment have a significant positive effect on managerial performance at PT Semen Padang.